226k views
3 votes
Passes through
(-6, 13) and (3, 1).

User Nonbeing
by
5.2k points

1 Answer

6 votes

Final answer:

The equation of the line that passes through the points (-6, 13) and (3, 1) is (4/3)x + y = 5.

Step-by-step explanation:

To find the equation of the line that passes through the points (-6, 13) and (3, 1), we can use the point-slope form. The point-slope form of a linear equation is y - y1 = m(x - x1), where (x1, y1) is a point on the line and m is the slope of the line. First, we need to find the slope:

m = (y2 - y1) / (x2 - x1)

Plugging in the coordinates, we get:

m = (1 - 13) / (3 - (-6))

m = -12/9

Simplifying, we get:

m = -4/3

Now that we have the slope, we can choose one of the points and the slope to write the equation:

y - y1 = m(x - x1)

Using the point (-6, 13):

y - 13 = (-4/3)(x - (-6))

Simplifying, we get:

y - 13 = (-4/3)(x + 6)

Expanding, we get:

y - 13 = (-4/3)x - 8

Finally, rearranging the equation to the standard form, we get:

(4/3)x + y = 5

User Anirudha Agashe
by
5.3k points